Social Support with Prevention Behaviors of Diseases and Occupational Accidents among Garbage Collectors, Bang Pa-In District, Phranakhon Sri Ayutthaya Province - รัตนาคณหุตานนท์ เฟื่องฟ้า; ดวงประทุม นาตยา (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The purposes of this cross-sectional survey study were to investigate; 1) the prevention behaviors of diseases and occupational accidents among garbage collectors, 2) the social support for garbage collectors, and 3) study the relationship between social support for garbage collectors and the prevention behaviors of diseases of garbage collectors, Bang Pa-In District, Phranakhon Sri Ayutthaya province. The research samples consisted of 154 garbage collectors who work in vehicle garbage transport. The research instrument was a questionnaire with personal data, social support and prevention behaviors scale. Statistical analysis was using frequency, percentage, mean, standard deviation, and Chi-square. The research findings were as follows; 1) Prevention behaviors of diseases and occupational accidents among garbage collectors were found at moderate level (mean = 2.14). 2) The social support for garbage collectors was found at a high level (mean = 2.50). 3) Social support from family members, colleagues, and supervisors have relationship with prevention behaviors of diseases and occupational accidents among garbage collectors at Bang Pa-In District, Phra Nakhon Sri Ayutthaya Province at the level of .05.